Nitrogen Isotopes in the Global Ocean - Somes, Christopher (2013)
Nitrogen is an essential nutrient for life. Its low abundance throughout much of the sunlit surface ocean limits the growth of primary producers that form the base of ocean ecosystems. Phytoplankton also consume surface ocean CO2 during growth, preventing this greenhouse gas from outgassing to the atmosphere where it will influence climate. Since the source and sink processes that control the balance of the bio-available nitrogen inventory, N2 fixation and denitrification/anammox (N-loss), respectively, are sensitive to climate, they may have an important feedback on atmospheric CO2 during climate change. N2 fixation and N-loss processes leave a distinguishable imprint on the ratio of stable nitrogen isotopes, δ15N, making it a useful tracer to constrain their patterns and rates. This dissertation incorporates δ15N into an Earth System Climate Model to better understand and quantify important N-cycling processes in the ocean. The two stable nitrogen isotopes, 14N and 15N, are included as prognostic tracers into the ocean biogeochemistry component of an Earth System Climate Model. A global database of δ15NO3− observations is compiled from previous studies and compared to the model results. The model is able to qualitatively and quantitatively reproduce many of the observed patterns such as high subsurface values in water column denitrification zones, low values in the North Atlantic attributed to N2 fixation, and the meridional and vertical gradients in the Southern Ocean caused by phytoplankton NO3− assimilation. Experiments show the most important isotope effects that drive the global distribution of δ15N are phytoplankton NO3− assimilation, N2 fixation, and denitrification/anammox. Nitrogen isotopes trends across the Pacific Ocean support that aeolian iron deposition is an important factor regulating the distribution of N2 fixation. N2-fixers have high structural iron requirements in their N2-fixing enzyme, which could restrict their growth since iron is a limiting micronutrient. Model experiments with and ...